Applying Kitab ‘Abbir Lughataka! Based on Communicative Approach in Muhādatsah Usbū’iyyah Program at Pesantren Daarul Uluum Bogor - Tamam, Muhammad Ibnu; Mufidah, Nuril; Rosyidi, Abdul Wahab; Waro, Ruhamaul; Zaeni, Rahmania Auriel; Nuzula, Alfiyah Firdausi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
The focus of this article is to find out an overview of the applying kitab 'Abbir Lughataka! based on a communicative approach in muhādatsah usbū'iyyah activities at the Daarul Uluum Bogor Islamic Boarding School and identifying its impact on improving students' speaking skills. The subject of this study is a 9th-grade student of madrasah Tsanawiyah Islamic boarding school Daarul Uluum Bogor using the muhadatsah guidebook 'Abbir Lughataka! Based on a communicative approach in muhādatsah usbū'iyyah activities. The research used in this paper is a descriptive qualitative approach with field research where data is collected through observation and interviews. Then in analyzing the data, qualitative descriptive analysis is used which includes several stages, namely data collection, data reduction, data presentation, and conclusion. The results of the study concluded that from the results of the implementation of the muhadatsah guidebook 'Abbir Lughataka! based on a communicative approach to grade 9 students of Madrasah Tsanawiyah Daarul Uluum Islamic Boarding School Bogor in the activities of the muhādatsah usbū'iyyah program, has proven to have a positive impact on improving the speaking skills (maharah kalam) of students. This is evidenced by the results of an evaluation test trial through an oral exam (ikhtibār syafahiy) to measure the Arabic speaking skills of students after learning for approximately four weeks. Keywords: Guidebook, Muhadatsah, Communicative Approach, Maharah Kalam